2009
DOI: 10.1051/0004-6361/200811376
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind elemental abundances related to the Sun's open magnetic flux

Abstract: Context. We present an investigation of the effects of solar magnetic field on the elemental abundance ratios of heavy ions in the solar wind. Aims. We compare the elemental abundance ratios Fe/O, Si/O, Mg/O, Ne/O, and C/O over the 23rd solar cycle, attention being given to the varying fraction of open magnetic flux on the visible side of the solar disc. Methods. We use ACE solar wind data, the current sheet source surface (CSSS) model of the corona, and SoHO/MDI data to relate solar wind compositional propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Since anemone ARs form only in the unipolar field of CHs, it is plausible that they would have lower FIP bias levels compared with ARs surrounded by mixed polarity QS plasma of higher FIP bias, assuming other factors such as age are similar between the ARs. This is consistent with the results of Wang et al (2009), who found that over solar cycle 23, the average enrichment factor compared to photospheric values for a group of low FIP elements, including Si, was only 1.7-2.5 when the fraction of open flux on the visible side of the solar disk exceeded 14%, however, the en- richment factor increased to 2.8-4.2 when the open flux fraction was less than 7%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since anemone ARs form only in the unipolar field of CHs, it is plausible that they would have lower FIP bias levels compared with ARs surrounded by mixed polarity QS plasma of higher FIP bias, assuming other factors such as age are similar between the ARs. This is consistent with the results of Wang et al (2009), who found that over solar cycle 23, the average enrichment factor compared to photospheric values for a group of low FIP elements, including Si, was only 1.7-2.5 when the fraction of open flux on the visible side of the solar disk exceeded 14%, however, the en- richment factor increased to 2.8-4.2 when the open flux fraction was less than 7%.…”
Section: Discussionsupporting
confidence: 92%
“…Elemental abundances of the Sun and their spatial and temporal variations are crucial to our understanding of the physical processes inherent to space weather as they can be used to probe the source regions of the solar wind (SW) and to trace the SW throughout interplanetary space. Furthermore, composition can provide clues to the magnetic topology of the SW source regions as plasma on open magnetic fields can be distinguished from plasma confined in closed loops (Woo et al 2004;Laming 2004;Wang et al 2009). As demonstrated by van Driel-Gesztelyi et al (2012), the magnetic topology of active regions (ARs) bordering coronal holes has significant implications for coronal outflows and the SW.…”
Section: Introductionmentioning
confidence: 99%